2022
DOI: 10.1177/27325016221082229
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Skeletal Anterior Open Bite Malocclusion on Speech

Abstract: Introduction: Articulation problems are seen in 80% to 90% of dentofacial deformity (DFD) subjects compared with 5% of the general population, impacting communication and quality of life, but the causal link is unclear. We hypothesize there are both qualitative (perceptual) and quantitative (spectral) differences in properties of stop (/t/ or /k/), fricative (/s/ or /ʃ/), and affricate (/tʃ/) consonant sounds and that severity of anterior open bite (AOB) jaw disharmonies correlates with degree of speech abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 31 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…The findings of the present investigation are in line with studies by Al-Balkhi Zah-rani and Al-Emran et al .,[ 43 ] which concluded that Class I malocclusion was the most typical type of malocclusion seen in the Saudi population followed by Class II division I and Class III. [ 37 43 44 45 ] According to Abdullah MA, the dental malocclusion which is prevalent in the Saudi population is Angle's Class I, followed by asymmetrical molar relationship in patients with AOBs. A small sample size and the inclusion of only participants who reported to a private dental institution are few limitations of the study.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the present investigation are in line with studies by Al-Balkhi Zah-rani and Al-Emran et al .,[ 43 ] which concluded that Class I malocclusion was the most typical type of malocclusion seen in the Saudi population followed by Class II division I and Class III. [ 37 43 44 45 ] According to Abdullah MA, the dental malocclusion which is prevalent in the Saudi population is Angle's Class I, followed by asymmetrical molar relationship in patients with AOBs. A small sample size and the inclusion of only participants who reported to a private dental institution are few limitations of the study.…”
Section: Resultsmentioning
confidence: 99%
“…An articulation disorder is a type of SSD characterized by “atypical production of speech sounds characterized by substitutions, omissions, additions or distortions that may interfere with intelligibility” [ 10 ]. Articulation disorders are often seen in DFD patients with severe malocclusions and jaw disproportions [ 19 , 26 , 44 ]. Starting at age seven, the American Association of Orthodontics (AAO) recommends that children be referred to an orthodontist for an initial evaluation [ 45 ].…”
Section: Speech and Craniofacial Developmentmentioning
confidence: 99%
“…Severe malocclusion has been implicated as a cause of speech distortion, especially in the pronunciation of sibilants [s] and [z] [ 44 46 ]. Linear correlations have been found between the severity of malocclusion and the degree of distortion, suggesting causation between malocclusion and speech distortions [ 19 , 26 , 44 ].…”
Section: Effects Of Malocclusion On Speechmentioning
confidence: 99%
See 2 more Smart Citations